Biological imaging using light-addressable potentiometric sensors and scanning photo-induced impedance microscopy. (3rd May 2017) - Wu, Fan; Campos, Inmaculada; Zhang, De-Wen; Krause, Steffi
Abstract : Light-addressable potentiometric sensors (LAPS) and scanning photo-induced impedance microscopy (SPIM) use photocurrent measurements at electrolyte–insulator–semiconductor substrates for spatio-temporal imaging of electrical potentials and impedance. The techniques have been used for the interrogation of sensor arrays and the imaging of biological systems. Sensor applications range from the detection of different types of ions and the label-free detection of charged molecules such as DNA and proteins to enzyme-based biosensors. Imaging applications include the temporal imaging of extracellular potentials and dynamic concentration changes in microfluidic channels and the lateral imaging of cell surface charges and cell metabolism. This paper will investigate the current state of the art of the measurement technology with a focus on spatial and temporal resolution and review the biological applications, these techniques have been used for. An outlook on future developments in the field will be given.